2013
DOI: 10.1364/ol.38.002113
|View full text |Cite
|
Sign up to set email alerts
|

MgZnO p–n heterostructure light-emitting devices

Abstract: MgZnO heterostructure light-emitting devices (LEDs) have been fabricated from p-Mg(0.35)Zn(0.65)O/n-Mg(0.20)Zn(0.80)O structures, and the p-type Mg(0.35)Zn(0.65)O film was realized using a lithium-nitrogen codoping method. Obvious ultraviolet emission peaked at around 355 nm dominates the electroluminescence (EL) spectra of the device at room temperature, which comes from the near-band-edge emission of the n-type Mg(0.20)Zn(0.80)O film. This is the first report on MgZnO heterostructured LEDs and the shortest E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The substrate temperature was kept at 650°C and the pressure in the growth chamber was kept at 3 × 10 3 Pa during the growth process. The p-Mg 0.35 Zn 0.65 O layers were grown by the plasma-assisted molecular beam epitaxy technique (VG V80H) using a lithium and nitrogen codoping method [27][28][29] employing high-purity elemental zinc, magnesium, and lithium contained in Knudsen cells as Zn, Mg, and Li sources, respectively, and atomic oxygen and nitrogen generated from O 2 and NO gases via 13.56 MHz radio frequency plasma cells operated at 300 W as O and N sources, respectively. During the growth process, the pressure in the growth chamber was fixed at 2 × 10 −5 mbar and the O 2 and NO flow rate were maintained at 1.0 sccm and 0.9 sccm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate temperature was kept at 650°C and the pressure in the growth chamber was kept at 3 × 10 3 Pa during the growth process. The p-Mg 0.35 Zn 0.65 O layers were grown by the plasma-assisted molecular beam epitaxy technique (VG V80H) using a lithium and nitrogen codoping method [27][28][29] employing high-purity elemental zinc, magnesium, and lithium contained in Knudsen cells as Zn, Mg, and Li sources, respectively, and atomic oxygen and nitrogen generated from O 2 and NO gases via 13.56 MHz radio frequency plasma cells operated at 300 W as O and N sources, respectively. During the growth process, the pressure in the growth chamber was fixed at 2 × 10 −5 mbar and the O 2 and NO flow rate were maintained at 1.0 sccm and 0.9 sccm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in the material issues of Mg x Zn 1−x O thin films may lead to applications including MgZnO p-n heterostructure light-emitting devices that operate at 355 nm [14], plasmonic generation in Ga-doped MgZnO for solar cell technologies [15], and solar-blind UV detectors with a cutoff at 270 nm [16]. Additionally, it has been found that the MgZnO thin film transistors at the small Mg composition range Mg 0.06 Zn 0.94 O have better device performance than pure ZnO channel devices [17].…”
Section: Introductionmentioning
confidence: 99%
“…The study about a structured optical field with the inhomogeneous SoP and a special caustic phase in the field cross section still keeps a challenging regime. [16][17][18] In particular, whether the SoP can be flexibly manipulated and controlled during propagation in free space is a topic being pursued because of its potential applications and fundamental physics relevance. Recently, some researches about the spin separation of light and spin-dependent propagation have been demonstrated, [19,20] A desirable intensity pattern can be achieved by tailoring the initial SoP, [19] especially in relation with the spin Hall effect of light.…”
Section: Introductionmentioning
confidence: 99%